Understanding structures and practices of meaning-making in industrial networks. Issue 4 (3rd May 2016) - Lowe, Sid; Rod, Michel; Hwang, Ki-Soon
Abstract : Purpose: This paper aims to propose an approach for exploring industrial marketing network environments through a social semiotic lens. Design/methodology/approach: This conceptual paper introduces social semiotic perspectives to the study of business/industrial network interaction. Findings: This paper describes how structures of meaning derived from a cultural history of signification and interpretive processes of meaning in action are co-determined in social semiosis. The meaning of environments using this social semiotic approach is emphasised, leading us to explore the idea of the "atmosemiosphere" – the most highly complex business network level, in illustrating how meaning is made through structuration between structures of meaning and their enactments in interactions between actors within living business networks. Practical Implications: Figurative language plays an important role in the structuration of meaning. This facilitates establishing plots and, therefore, in the actors' capability to tell a story, which starts with knowing what kind of story can be told. By implication, the effective networker must be a consummate moving "picture maker" and, to do so, she must have competence in narrative, emplotment, myth-making, storytelling and figuration in more than one discursive repertoire. Originality/value: In using a structurational discourse perspective informed by social semiotics, our original contribution is a "business networks as discursive constructions" approach, in that discursive nets, webs of narratives and stories and labyrinths of tropes are considered just as important in constituting networks as networks of actor relationships and patterns of other activities and resources.